Continuing the study of Islamic Civilization is imperative as it incorporates the functionalist confluences between different faiths and belief systems in Malaysia - Nur Azuki Yusuff; Kevin Fernandez; Nik Yusri Musa (2014)
The rational of maintaining the Study of Islamic Civilization or TITAS is due to the consideration of integrating a society, which is committed to the mutual understanding of different belief systems in view of living harmoniously. This paper posits the Functionalist proposition of the Islamic religion as an axis since it is the official religion of the Malaysian state and the points of confluences with other belief systems in Malaysia such as Chritianisty, Hinduism, Buddhism, Sikhism, Confusism, Taoism and that holds to the similar ‘functionalist’ ideologies such as human rights, heritage, harmony, safety and unity while considering universal moral values such as: good faith, being considerate, virtuous, honest, diligent, cooperative and high sense of community living especially in managing conflict of opinions. This paper proposes a few areas of emphasis to be taken into consideration when teaching this subject to further strengthen the function of Islam in teaching TITAS.